NEUROPROTECTIVE EFFECT OF METHANOLIC EXTRACT OF SARGASSUM WIGHTII ON HALOPERIDOL INDUCED CATALEPSY AND TARDIVE DYSKINESIA IN ALBINO RATS - ROUT, S.; RATH, B.; BHATTAMISRA, S. K.; KUMAR, A.; RATH, S. (International Journal of Pharmacy and Pharmaceutical Sciences, 2020)
Objective: The present study was designed to evaluate the neuroprotective effect of methanolic extract of Sargassum wightii on haloperidol-induced catalepsy and tardive dyskinesia in Wistar albino rats. Methods: In this study, thirty Wistar albino rats were randomly divided into six groups. Gr-I served as control. Haloperidol (1 mg/kg intraperitoneally) was administered to rats of Gr-II to Gr-V for twenty-one consecutive days to induce catalepsy and tardive dyskinesia. Animals of Gr-II to Gr-V were orally administered with vehicle, levodopa carbidopa combination (30 mg/kg), Sargassum extract 200 and 400 mg/kg respectively. All the drugs and vehicles were given orally one hour before haloperidol injection for twenty one consecutive days. The cataleptic scores were recorded using standard bar test. Tardive dyskinesia was assessed in terms of vacuous chewing movement (VCM) and tongue protrusion (TP) scores. After behavioural testing, all animals were sacrificed on twenty-second day and various biochemical parameters like MDA, SOD and GSH were estimated in brain tissue. Results: Chronic administration of haloperidol significantly increased cataleptic scores, VCM and TP scores. (p<0.001) Sargassum wightii extract (400 mg/kg) significantly inhibited haloperidol-induced catalepsy, VCM and TP (p<0.001) Haloperidol increased MDA and decreased SOD and GSH in brain tissue to a highly significant extent (p<0.001) Sargassum extract at 400 mg/kg also significantly reversed the haloperidol-induced alteration in brain oxidative stress markers. Conclusion: Sargassum wightii inhibits haloperidol-induced catalepsy and tardive dyskinesia. Thus it may be used as a unique therapeutic adjunct for the prevention of neuroleptic-induced extrapyramidal symptoms, however, it has to be explored more.